2022
DOI: 10.1002/anie.202115805
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Carboxylic Acid Isosteres and Prodrugs for Inhibition of the Human SIRT5 Lysine Deacylase Enzyme**

Abstract: Sirtuin 5 (SIRT5) is a protein lysine deacylase enzyme that regulates diverse biology by hydrolyzing ϵ‐N‐carboxyacyllysine posttranslational modifications in the cell. Inhibition of SIRT5 has been linked to potential treatment of several cancers but potent compounds with activity in cells have been lacking. Here we developed mechanism‐based inhibitors that incorporate isosteres of a carboxylic acid residue that is important for high‐affinity binding to the enzyme active site. By masking of the tetrazole moiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 63 publications
3
29
0
Order By: Relevance
“…Among SIRT5 inhibitors, a great deal of work has been carried out starting from peptide substrate analogues, which has led to promising peptide-based inhibitors. These consist of thiourea-based molecules such as 2c , 135 3b , 3d , 155 and 3i , 148 which display submicromolar SIRT5 inhibition ( Table 2 ). These molecules were all administered as prodrugs to mask the negative charge of the carboxylic group and increase cellular permeability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among SIRT5 inhibitors, a great deal of work has been carried out starting from peptide substrate analogues, which has led to promising peptide-based inhibitors. These consist of thiourea-based molecules such as 2c , 135 3b , 3d , 155 and 3i , 148 which display submicromolar SIRT5 inhibition ( Table 2 ). These molecules were all administered as prodrugs to mask the negative charge of the carboxylic group and increase cellular permeability.…”
Section: Discussionmentioning
confidence: 99%
“… 147 In line with this, SIRT5 knockdown decreases colony formation and enhances apoptosis in a wide range of AML cell lines, and the pharmacological inhibition of SIRT5 impairs cell proliferation and induces apoptosis in SIRT5-dependent AML cells such as OCI-AML2, SKM-1, and MOLM-13 (see compounds 3b , 3d , and 3i , respectively, in section 4.1 ). 147 , 148 Similarly, SIRT5 expression is necessary for tumor insurgence and growth in both xenograft and syngeneic AML mouse models. 147 Finally, a recent study also revealed that the tumor suppressor p53 is succinylated at Lys120; 149 this residue was also previously identified as an acetylation site of KAT8, Tip60, and NAT10.…”
Section: Biological Activities and Disease Relevance Of Sirt5mentioning
confidence: 99%
See 2 more Smart Citations
“…This peptide became the lead compound for a series of optimization campaigns, carried out by different research groups. In 2022, Rajabi and co-workers investigated isostere and prodrug derivatives of 32, modified at the carboxylic function [55]. In a BioRxiv preprint, Bolding et al reported the study of fluorosulfate analogues, with po- Many other research groups investigated thiourea derivatives, albeit with more modest success.…”
Section: Synthetic Compoundsmentioning
confidence: 99%